Atomic origins of the strong metal–support interaction in silica supported catalysts. Issue 38 (31st August 2021) - Yang, Feng; Zhao, Haofei; Wang, Wu; Wang, Lei; Zhang, Lei; Liu, Tianhui; Sheng, Jian; Zhu, Sheng; He, Dongsheng; Lin, Lili; He, Jiaqing; Wang, Rongming; et al.
Abstract : This work tracked at the atomic scale the interfacial reaction induced strong metal–support interaction between SiO2 and metal catalysts and evolution under reactive conditions by aberration-corrected environmental transmission electron microscopy. Abstract : Silica supported metal catalysts are most widely used in the modern chemical industry because of the high stability and tunable reactivity. The strong metal–support interaction (SMSI), which has been widely observed in metal oxide supported catalysts and significantly affects the catalytic behavior, has been speculated to rarely happen in silica supported catalysts since silica is hard to reduce. Here we revealed at the atomic scale the interfacial reaction induced SMSI in silica supported Co and Pt catalysts under reductive conditions at high temperature using aberration-corrected environmental transmission electron microscopy coupled with in situ electron energy loss spectroscopy. In a Co/SiO2 system, the amorphous SiO2 migrated onto the Co surface to form a crystallized quartz-SiO2 overlayer, and simultaneously an interlayer of Si was generated in-between. The metastable crystalline SiO2 overlayer subsequently underwent an order-to-disorder transition due to the continuous dissociation of SiO2 and the interfacial alloying of Si with the underlying Co. The SMSI in the Pt–SiO2 system was found to remarkably boost the catalytic hydrogenation. These findings demonstrate the universality of the SMSI in oxide supported catalysts, which is of general importance for designing catalysts and understanding catalytic mechanisms.